A Phase II Single Arm Pilot Study of the CHK1 Inhibitor Prexasertib (LY2606368) in BRCA Wild‐Type, Advanced Triple‐Negative Breast Cancer. (24th June 2020) - Gatti‐Mays, Margaret E.; Karzai, Fatima H.; Soltani, Sanaz N.; Zimmer, Alexandra; Green, Jeffrey E.; Lee, Min‐Jung; Trepel, Jane B.; Yuno, Akira; Lipkowitz, Stanley; Nair, Jayakumar; McCoy, Ann; Lee, Jung‐Min
Abstract: Lessons Learned: Monotherapy with prexasertib demonstrated modest activity in BRCA wild‐type, recurrent triple‐negative breast cancer, highlighting the unmet need for combination treatment strategies. Neutropenia, anemia, and thrombocytopenia are common with the use of prexasertib but are manageable with supportive care measures. Prophylactic use of granulocyte colony stimulating factor should be considered to avoid dose reductions or treatment delays. Pharmacodynamic studies showed prexasertib treatment induced DNA damage in peripheral immune cells. Background: Cell cycle checkpoint kinase 1 (CHK1) is a major G2/M cell cycle regulator in tumors with p53 dysfunction, such as triple‐negative breast cancer (TNBC). We hypothesized the second‐generation CHK1 inhibitor, prexasertib, would yield clinical activity in sporadic TNBC. Methods: This single arm, phase II trial evaluated prexasertib at 105 mg/m 2 IV every 2 weeks in patients with metastatic/recurrent TNBC. The primary endpoint was overall response rate (ORR). Results: All nine patients enrolled were germline BRCA wild‐type ( BRCA wt) and had at least one prior treatment. One partial response (PR) was observed (ORR of 11.1%). Four patients experienced stable disease. The median progression‐free survival (PFS) was 86 days (range 17 to 159 days). Grade 3/4 treatment‐related adverse events included afebrile neutropenia ( n = 8; 88.9%), anemia ( n = 3; 33.3%), and thrombocytopenia ( n = 1; 11.1%). Pharmacodynamic studies showed prexasertib treatment induced DNA damage in peripheral immune cells and demonstrated a decrease in activated/reinvigorated CD8 T cells; however, the one patient with a PR showed evidence of T‐cell recovery. Conclusion: Prexasertib monotherapy had modest clinical efficacy in BRCA wt TNBC. Further studies of prexasertib in combination with other agents are needed.